EFFECTIVE COMMUNICATION ROLE OF SECRETARIES IN CAMPUS ORGANIZATIONS - Jenny Helvira; Ayudira, Rani Syahfitri, Rita Hartati (Adisam Publisher, 2025)
This study examines the role of secretaries in eflective communication within campus organizations, focusing on their contributions to problem-solving and decision- making. The research, based on a survey of secretaries, highlights the frequency of communication, problem identification methods, and the eflectiveness of communication in conflict resolution. The findings suggest that while frequent communication promotes transparency and collaboration, its quality is essential for clarity and impact. Challenges like misunderstandings and communication barriers emphasize the need for targeted training in conflict resolution, persuasive communication, and strategic decision-making. The study concludes that focused professional development can significantly enhance secretaries' communication skills, improving organizational practices and outcomes.